Effects and interactions of dietary lysine and apparent nitrogen corrected metabolizable energy on yellow-feathered broiler breeder hens - Yibing Wang; Qin Wang; Xiangtian Yao; Zhongyong Gou; Xiajing Lin; Qili Luo; Shouqun Jiang (Journal of Animal Science and Biotechnology)
Abstract Background Dietary lysine and apparent nitrogen-corrected metabolizable energy (AMEn) are two key variables affecting the production of breeder hens. In this study, the effects and interactions of lysine and AMEn on yellow-feathered broiler breeder hens were investigated. A total of 720 30-week-old breeder hens were fed in a 5 (lysine: 0.56%, 0.68%, 0.80%, 0.92%, and 1.04%) × 2 (AMEn: 11.50 and 11.10 MJ/kg) factorial arrangement for 12 weeks. The productive performance, reproductive traits, biochemical variables of breeder hens, the amino acid concentration and quality of eggs, and the growth performance of offspring broilers were determined. Result (1) Dietary lysine had quadratic effects (P < 0.05) on laying rate, average daily egg mass and feed intake/egg mass of breeder hens; birds with 11.50 MJ/kg AMEn (high AMEn) had higher (P < 0.05) BW than those with 11.10 MJ/kg AMEn (low AMEn); (2) dietary lysine significantly affected on the relative ovarian weight (quadratic and linear), and numbers of large yellow follicles (LYF, quadratic); birds with high AMEn had longer fallopian tube and more LYF than those with low AMEn (P < 0.05); (3) dietary lysine had significant effects (linear and quadratic) on eggshell thickness and shell strength of eggs from breeder hens; birds with high AMEn had thinner eggshells and deeper yolk color than those with low AMEn (P < 0.05); (4) there were higher (P < 0.05) contents of protein and concentrations of all measured animo acids (AAs) in eggs from birds fed low AMEn; (5) supplementation with high AMEn to breeder hens significantly increased the hatchability of fertilized eggs; (6) neither dietary lysine level or AMEn affected growth performance of offspring broilers; (7) both dietary lysine level and AMEn significantly affected gonadotropin concentrations and biochemical variables of breeder hens. Conclusions Dietary lysine had significant influences on productive performance, reproductive traits, and egg quality of yellow-feathered breeder hens. Based on productive performance, the optimal levels of dietary lysine were 0.81% to 0.83%, while 0.71% to 72% lysine was enough to obtain the best quality of breeding eggs. High AMEn was more beneficial to breeder hens for reproductive traits and hatchability of the fertilized eggs, while it showed detrimental effects on eggshell thickness and AA concentrations of breeding eggs.